2020
DOI: 10.3390/nano10020376
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide–Silver Nanoparticle Nanohybrids: Synthesis, Characterization, and Antimicrobial Properties

Abstract: Drug resistance of pathogenic microorganisms has become a global public health problem, which has prompted the development of new materials with antimicrobial properties. In this context, antimicrobial nanohybrids are an alternative due to their synergistic properties. In this study, we used an environmentally friendly one-step approach to synthesize graphene oxide (GO) decorated with silver nanoparticles (GO–AgNPs). By this process, spherical AgNPs of average size less than 4 nm homogeneously distributed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 96 publications
(137 reference statements)
7
95
0
Order By: Relevance
“…Thus, the antibacterial efficacy of AgNP-GO with four NP sizes (10, 30, 50, and 80 nm) against E. coli and S. aureus has been tested, and its was found that the composite with the smallest NP showed the best activity [61]. Similarly, a recent study [62] investigated the bactericide action of AgNP-GO (ratio 1:2.3) manufactured via an environmentally friendly one-step approach, which comprised of spherical NPs with different diameters. The smallest NPs (ca.…”
Section: Nanocomposites With Silver Nanoparticlesmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, the antibacterial efficacy of AgNP-GO with four NP sizes (10, 30, 50, and 80 nm) against E. coli and S. aureus has been tested, and its was found that the composite with the smallest NP showed the best activity [61]. Similarly, a recent study [62] investigated the bactericide action of AgNP-GO (ratio 1:2.3) manufactured via an environmentally friendly one-step approach, which comprised of spherical NPs with different diameters. The smallest NPs (ca.…”
Section: Nanocomposites With Silver Nanoparticlesmentioning
confidence: 89%
“…To solve this issue, nanocomposites of graphene and Ag nanoparticles were developed [49,50], although the improvements in antibacterial activity were still limited. Therefore, numerous studies have been reported on GO and rGO nanocomposites comprising Ag nanoparticles [51][52][53][54][55][56][57][58][59][60][61][62] (Table 1), showing improved performance compared to GO and Ag nanoparticles alone due to synergistic effects; further, the mixture of both constituents considerably reduces the concentrations required to inhibit all bacteria. Thus, significantly higher antibacterial activity was found for AgNPs-GO composites (1:2 ratio), with an average NP size of 80 nm [52] at a concentration of 200 µg/mL (Table 1), compared to that of GO or AgNPs, attributed to a higher ROS production, hence resulting in stronger oxidative stress and disruption of the cell membrane.…”
Section: Nanocomposites With Silver Nanoparticlesmentioning
confidence: 99%
“…Details of the synthesis are described in the Supplementary Materials (Preparation of Graphene Oxide (GO)). We used the in situ approach for the synthesis of GO-AgNPs hybrid, which consists of simultaneous reduction of metal salt and GO using L-AA as a green reductant as described in our previous work [42]. Briefly, an aqueous dispersion of graphite oxide (GrO) (0.5 mg/mL) was sonicated for 1 h to obtain GO.…”
Section: Synthesis Of Graphene Oxide (Go) and Graphene Oxide-silver Nmentioning
confidence: 99%
“…Graphene and its derivative materials have relatively high specific surface area with abundant surface functionalities in case of graphene oxide, which have the potential for the preparation of multiple composite antibacterial materials in combination with other antimicrobial agents [20,21]. It has been proved the synergistic or additive effect of graphene derivatives with silver composite materials, leading an enhanced activity at low concentration [22][23][24][25]. Similarly, hybrid systems with ZnO and TiO 2 nanoparticles have demonstrated excellent antibacterial activity [26][27][28].…”
Section: Introductionmentioning
confidence: 99%